2018
DOI: 10.3389/fchem.2018.00372
|View full text |Cite
|
Sign up to set email alerts
|

Selectivity and Reactivity of ZrIV and CeIV Substituted Keggin Type Polyoxometalates Toward Cytochrome c in Surfactant Solutions

Abstract: In this paper we investigate the effect of three different types of surfactants, on the hydrolysis of Cytochrome c (Cyt c), a predominantly α helical protein containing a heme group, promoted by [Ce(α PW11O39)2]10- (CeK) and [Zr(α PW11O39)2]10- (ZrK) polyoxometalates. In the presence of SDS, Zw3 12, or CHAPS surfactants, which are commonly used for solubilizing hydrophobic proteins, the specificity of CeK or ZrK toward hydrolysis of Cyt c does not change. However, the hydrolysis rate of Cyt c by CeK was increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
51
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(54 citation statements)
references
References 92 publications
(99 reference statements)
2
51
1
Order By: Relevance
“…However, in the case of ac onsiderably smaller globular protein, Cyt c, which consists of 104 amino acids, it was demonstrated that the addition of surfactants caused largec hanges in the tertiary structure of the protein, which prevented effective interactions with the POM and resulted in ad ecrease in the protein hydrolysis rate. [73]…”
Section: Proposedmechanism Of B-casein Hydrolysis Bymentioning
confidence: 99%
“…However, in the case of ac onsiderably smaller globular protein, Cyt c, which consists of 104 amino acids, it was demonstrated that the addition of surfactants caused largec hanges in the tertiary structure of the protein, which prevented effective interactions with the POM and resulted in ad ecrease in the protein hydrolysis rate. [73]…”
Section: Proposedmechanism Of B-casein Hydrolysis Bymentioning
confidence: 99%
“…In the last few years our research group has been developing a new class of artificial metalloproteases based on metal-oxo-based materials and on metal-substituted polyoxometalates, which are able to selectively hydrolyze proteins under mild experimental conditions while producing larger peptide fragments [ 9 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. Polyoxometalates are a large class of inorganic metal-oxygen clusters which are composed of transition metals in their highest oxidation state.…”
Section: Introductionmentioning
confidence: 99%
“…The POM, [Zr(α-PW 11 O 39 ) 2 ] 10− (1), is used as the salt, (Et 2 NH 2 ) 10 [Zr(α-PW 11 O 39 ) 2 ] throughout the study. This POM has previously been shown to exhibit catalytic activity towards the hydrolysis of different proteins [13,14].…”
Section: Introductionmentioning
confidence: 96%
“…In the case of the hydrolysis of hydrophobic proteins, a common approach to circumvent the low solubility (or often insolubility) of the proteins in aqueous solution is to use surfactants. However, as the surfactants exhibit polar or charged headgroups, they can also be involved in a variety of electrostatic or hydrogen bonding interactions with the POM [13]. This could hinder the binding of the POM to a protein, or it could inhibit their catalytic activity [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation